2017
DOI: 10.4012/dmj.2015-382
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bioglass and silica coating of zirconia substrate on its bond strength to resin cement

Abstract: This study aimed to assess the effect of bioglass and silica coating of zirconia substrate on its bond strength to resin cement. A total of 120 specimens were used in this in-vitro, experimental study. Zirconia discs measuring 10×7×2 mm were cut from Y-TZP zirconia blocks, sintered, cleaned and received different surface treatments of sandblasting, bioglass powder coating+etching, bioglass powder coating+etching+silanization, bioglass slurry coating+etching, bioglass slurry coating+etching+silanization, silica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Although many dental techniques [32] have been extensively investigated to improve the bond strength of resin to zirconia ceramics, there is no established protocol that can produce a stable bond which can be easily used at the present time. To achieve higher retention, prevent micro-leakage, and increase the fracture and fatigue resistance of restorations, many studies are under way [13, 26, 27]. However, the subpressure infiltration technique has not been applied in the dental adhesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many dental techniques [32] have been extensively investigated to improve the bond strength of resin to zirconia ceramics, there is no established protocol that can produce a stable bond which can be easily used at the present time. To achieve higher retention, prevent micro-leakage, and increase the fracture and fatigue resistance of restorations, many studies are under way [13, 26, 27]. However, the subpressure infiltration technique has not been applied in the dental adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Many surface treatments have been used to improve the bond strength of resin to zirconia ceramics over the past two decades, including air abrasion [11], diamond burs abrasion [12], silica (tribochemical) coating [13], silicoating [14, 15],selective infiltration etching [16] and laser [17, 18]. However, many studies have found microscopic cracks because these surface treatments can accelerate tetragonal-to-monoclinic (t→m) phase transformation [1922], and other researchers found that airborne particle abrasion decreased micro tensile bond strength [23].…”
Section: Introductionmentioning
confidence: 99%
“…Polymers can be used as a reinforcing agents, as in the study of Montazeri et al [41] which covers a nBG (nano-bioglass) scaffold with poly-3-hydroxybutyrate (P3HB), increasing the compressive strength and compressive modulus which is directly proportional to the immersion time in the polymer. Recently, Moezzizadeh et al [5] found that using bioglass as coating on zirconia implants enhance the bond strength to resin cement. This increase could be attributed to the higher surface roughness in the etched bioglass-coated surface.…”
Section: Compositional Features Mechanical Properties and Applicationsmentioning
confidence: 98%
“…Micro and nano-particles have superior bioactive behaviours due to a larger specific surface area that allows a faster ion release. Bioactive coatings are likewise very important for metallic implants because they have the potential to improve their performance by providing strong bonding to the host bone and to the resin cement [5]. Nevertheless, 45S5 bioglasses are applied also to non-permanent materials especially used in dentistry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation